Dynamic relationships among green bonds, CO2 emissions, and oil prices - Marín-Rodríguez, Nini Johana; González-Ruiz, Juan David; Botero, Sergio (Frontiers in Environmental Science, 2022)
Green bonds play a pivotal role in the financing of sustainable infrastructure systems. Likewise, CO2 emissions and oil prices can cause an impact on the green bonds market. In order to better understand this issue, this study analyzes the relationship among green bonds, CO2 futures’ price, and oil prices using a daily data set that includes 2206 observations corresponding to daily information from January 1, 2014 to June 15, 2022. The Granger Causality Test and the Dynamic Conditional Correlation (DCC-Garch) Model were employed to conduct this analysis. The Granger Causality Test results present a unidirectional causality running from the Green Bond Index to the oil price returns. Also, there is a unidirectional causality running from the Green Bond Index to the CO2 futures’ returns. Additionally, a unidirectional causality runs from the oil price returns to the CO2 futures’ returns. The results for the DCC-Garch indicate a positive dynamic correlation between the Brent oil price return and the CO2 futures’ returns. Finally, the Green Bond Index shows a negative dynamic correlation to the oil return and the CO2 futures’ returns presenting a strong correlation in uncertainty periods. This study represents a breakthrough in explaining the relationship among these variables.